2001
DOI: 10.1016/s0925-4773(01)00356-2
|View full text |Cite
|
Sign up to set email alerts
|

Periostin (an osteoblast-specific factor) is expressed within the embryonic mouse heart during valve formation

Abstract: Periostin was originally isolated as a osteoblast-specific factor that functions as a cell adhesion molecule for preosteoblasts and is thought to be involved in osteoblast recruitment, attachment and spreading. Additionally, periostin expression has previously been shown to be significantly increased by both transforming growth factor beta-1(TGFbeta1) and bone morphogenetic protein (BMP)-2. Likewise the endocardial cushions that form within embryonic heart tube (embryonic day (E)10-13) are formed by the recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(202 citation statements)
references
References 19 publications
5
196
0
1
Order By: Relevance
“…However, one interesting possibility is that periostin functions as a key downstream effector of TGF-β that promotes its deleterious effects in MD (31). Indeed, in the absence of periostin, TGF-β appears to have a protective effect in MD disease progression by enhancing regeneration or by blunting other negative effects of this cytokine (14). The use of the TGF-β-blocking antibody worsened MD and resulted in greater functional decline in double-null mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one interesting possibility is that periostin functions as a key downstream effector of TGF-β that promotes its deleterious effects in MD (31). Indeed, in the absence of periostin, TGF-β appears to have a protective effect in MD disease progression by enhancing regeneration or by blunting other negative effects of this cytokine (14). The use of the TGF-β-blocking antibody worsened MD and resulted in greater functional decline in double-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin expression is low at baseline in many adult tissues, but is strongly induced and secreted into the ECM after acute injury, as well as in dystrophic skeletal muscle (13). Periostin is expressed exclusively by fibroblasts or cells that adopt a fibroblast-like phenotype after an injurious event (14). In the heart, we and others have shown that periostin is strongly induced after myocardial infarction and left ventricular pressure overload, where it plays a role in ECM remodeling and healing (15,16).…”
mentioning
confidence: 98%
“…17 Periostin has a dynamic expression profile in both the developing heart and in adult tissue where it is induced during active remodeling or active stress. 16,18,19 Periostin is almost exclusively expressed by fibroblasts or cells that adopt fibroblast-like characteristics following injury. As a secreted protein associated with areas of fibrosis, periostin directly interacts with other ECM proteins, such as fibronectin, tenascin-C, collagen, and heparin.…”
Section: Introductionmentioning
confidence: 99%
“…Periostin is required for normal collagen architecture during heart valve development and lack of periostin resulted in valve leaflet thickening and matrix dysregulation in adult mice. [42][43][44] FSP1 is a very selective and effective biomarker for cardiac fibroblasts, 45 and most HAVIC express FSP1. 46 ADMSC in GM had significantly lower expression of vimentin and aSMA compared with pHAVIC (Fig.…”
Section: Expression Of Vic Markers In Admmsc Bmmsc and Havicmentioning
confidence: 99%